2018
DOI: 10.2147/ijn.s143506
|View full text |Cite
|
Sign up to set email alerts
|

Development of dihydrochalcone-functionalized gold nanoparticles for augmented antineoplastic activity

Abstract: BackgroundPhloridzin, an antidiabetic and antineoplastic agent usually found in fruit trees, is a dihydrochalcone constituent that has a clinical/pharmaceutical significance as a sodium-glucose linked transport 2 (SGLT2) inhibitor. While the aglycone metabolite of phloridzin, phloretin, displays a reduced capacity of SGLT2 inhibition, this nutraceutical displays enhanced antineoplastic activity in comparison to phloridzin.PurposeThe objective of this study was to develop gold nanoparticle (AuNP) mediated deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…From natural sources, dihydrochalcones are isolated as aglycones and their glycosides.Most extensively described dihydrochalcones are phloretin and its 2 -O-glucoside named phloridzin, isolated from a genus of small trees and shrubs Malus. Many studies proved numerous biological activities of phloridzin, such as anti-diabetic, anti-inflammatory, anti-oxidant, antihyperglycemic, antimicrobial, cardio-and hepatoprotective, anti-obesity and others [18][19][20][21][22]. Similar activities have been reported for phloretin [23].…”
Section: Introductionsupporting
confidence: 55%
“…From natural sources, dihydrochalcones are isolated as aglycones and their glycosides.Most extensively described dihydrochalcones are phloretin and its 2 -O-glucoside named phloridzin, isolated from a genus of small trees and shrubs Malus. Many studies proved numerous biological activities of phloridzin, such as anti-diabetic, anti-inflammatory, anti-oxidant, antihyperglycemic, antimicrobial, cardio-and hepatoprotective, anti-obesity and others [18][19][20][21][22]. Similar activities have been reported for phloretin [23].…”
Section: Introductionsupporting
confidence: 55%
“…In general, the results showed that LSTE, F1, F2 and their Au NPs had the potential to be used as antidiabetic agents. Pure isolated phytochemicals have demonstrated activities against alpha-glucosidase in previous studies [47,48]. Recently, Etsassala et al [89] reported a strong antidiabetic activity of ten abietane diterpenes.…”
Section: In-vitro Antidiabetic Studiesmentioning
confidence: 97%
“…Furthermore, since no external stabilizers were employed, it could also be concluded that the same constituents were responsible for the stabilization of the nanoparticles (see Scheme 1). Many investigations concluded that polyphenols, which are abundant in plants, are associated with the reduction of metal salts when combined with plant extracts [47,48]. This may also explain why F1 and F2 (which contain similar functionality) were not only able to reduce gold to its zero-valence state but also formed Au NPs with very similar characteristics to that of the LSTE.…”
Section: Uv-visible Spectroscopic Analysismentioning
confidence: 99%
See 2 more Smart Citations